Back Cover: Drastic Stabilization of Parallel DNA Hybridizations by a Polylysine Comb‐Type Copolymer with Hydrophilic Graft Chain (ChemMedChem 9/2014). Issue 9 (September 2014) - Miyoshi, Daisuke; Ueda, Yu‐mi; Shimada, Naohiko; Nakano, Shu‐ichi; Sugimoto, Naoki; Maruyama, Atsushi
<x xml:space="preserve">Abstract</x> The back cover picture shows the stabilization of parallel DNA hybrids by a polylysine comb‐type copolymer with a hydrophilic graft chain, which chemically mimics cationic proteins such as histones. The parallel conformations present in DNA duplexes and triplexes are significantly and specifically stabilized by the polymer, indicating that polycationic molecules are able to induce structural polymorphism of DNA oligonucleotides through conformation‐selective stabilization effects. For more details, see the Full Paper by Daisuke Miyoshi, Atsushi Maruyama et al. on p. 2156 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>